Reduction of Adverse Maternal Outcomes by Adequate Antenatal Care- Evidence In A Tertiary Care Hospital In Bangladesh - Mina, Mst Nazmunnaher; Areen, Samira; Habib, Mostafa Nahian; Rikta, Shamsun Nahar; Sultana, Jesmin; Azizi, Shajeda; Ahsan, Syeda Nafisa; Ahmed, Fabliha Fyrose; Shuchi, Ferdous Ara (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objective: The objective of the study is to assess the reduction of adverse maternal outcomes by adequate antenatal care Materials and methods: This cross-sectional study took place within the timeframe of January 2023 to August 2023 at the Department of Obstetrics and Gynecology, Delta Medical College Hospital in Dhaka, Bangladesh. Ethical approval was granted by the Institutional Review Board (IRB) of Delta Medical College Hospital. The study focused on 226 women who gave birth at the hospital during the specified period. A minimum of four antenatal care (ANC) visits were considered standard practice. The primary focus of the study was to examine the correlation between ANC visits and maternal outcomes. Result: The average age of the participants was 27.98±5.01 years, with 75.2% being housewives. Approximately 16% were married before the age of 18. Antenatal care from a registered physician was received regularly (e”4 visits) by over 87% of participants. Primigravida accounted for 33.6% of the participants, and more than 84% gave birth via cesarean section. Prevalence of preterm labor was found in 22.6% of the participants, 12.8% experienced premature rupture of membranes, gestational diabetes mellitus (12.4%), and hypertensive disorders during pregnancy (8.8%). A notable association was found between consistent antenatal care and positive maternal outcomes. Logistic regression analysis indicated that regular antenatal checkups act as a protective factor against adverse maternal outcomes. Pregnant women who received regular antenatal checkups encountered 62% less adverse maternal outcomes. so, we can state that 38% of pregnant women who did not receive regular antenatal checkups have the probability of encountering more adverse maternal outcomes. Conclusion: ANC care is an effective method for reducing adverse maternal outcome. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 84-91